2013
DOI: 10.1159/000348550
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Significance of Aberrant T-Cell Marker Expression on Diffuse Large B-Cell Lymphoma Cells

Abstract: Introduction: Aberrant expression of T-cell markers is occasionally observed in B-cell lymphomas. We conducted a retrospective study to establish its incidence and to determine its relationship with clinical features of patients with diffuse large B-cell lymphoma (DLBCL). Patients and Methods: We reviewed DLBCL patients diagnosed between January 2002 and April 2009. Patients fulfilled the following criteria: (1) age >18 years, (2) HIV negative, (3) B-cell lymphoma confirmed by restricted expression of surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…To our knowledge, no survival data of T-cell marker-positive DLBCL has been presented in a large number of patients (>150 patients) uniformly treated with R-CHOP-based chemotherapy. Suzuki et al [31] were the first to investigate prognostic implications of T-cell markers other than CD5 in DLBCLs, and they showed that such expression was not associated with outcome, consistent with the present findings. However, in the study by Suzuki et al , [31] the survival data for only 92 patients treated with rituximab-based chemotherapy were available, and the frequency of T-cell marker other than CD5expression was only assessed in the DLBCL population.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To our knowledge, no survival data of T-cell marker-positive DLBCL has been presented in a large number of patients (>150 patients) uniformly treated with R-CHOP-based chemotherapy. Suzuki et al [31] were the first to investigate prognostic implications of T-cell markers other than CD5 in DLBCLs, and they showed that such expression was not associated with outcome, consistent with the present findings. However, in the study by Suzuki et al , [31] the survival data for only 92 patients treated with rituximab-based chemotherapy were available, and the frequency of T-cell marker other than CD5expression was only assessed in the DLBCL population.…”
Section: Discussionsupporting
confidence: 90%
“…Suzuki et al [31] were the first to investigate prognostic implications of T-cell markers other than CD5 in DLBCLs, and they showed that such expression was not associated with outcome, consistent with the present findings. However, in the study by Suzuki et al , [31] the survival data for only 92 patients treated with rituximab-based chemotherapy were available, and the frequency of T-cell marker other than CD5expression was only assessed in the DLBCL population. Additionally, in the survival analysis, only T-cell markers other than CD5 were evaluated, and co-expression of CD5 was not demonstrated.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…is means that clonally restricted B-cells in our DLBCL case express CD7. Suzuki et al reported that aberrant T-cell marker expression detected by FCM could be confirmed in some, but not in all, cases detected by IHC [6]. ey reported that among 6 CD7positive cases by FCM, only 3 were confirmed to be positive for CD7 by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there was no significant difference in prognosis between T-cell marker-positive DLBCL other than CD5 and T-cell marker-negative DLBCL. Furthermore, Suzuki et al reported 150 cases of DLBCL; however, the clinicopathological significance and prognosis of CD7 in DLBCL are still unknown [6].…”
Section: Case Reports In Hematologymentioning
confidence: 99%